2021
DOI: 10.1002/jcop.22610
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial benefits and costs of activism among female migrant domestic workers in southern Spain

Abstract: Economic migrant women often experience oppressive living and working conditions in the receiving societies. Activism is a liberatory behavior these women may employ to transform such situations. This study explores the activism experience of female migrant domestic workers from Latin America settled in southern Spain, in terms of its psychosocial benefits and costs. A purposeful sample of eleven activist migrant women engaged in a grassroots organization of domestic workers and eight members of social organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 62 publications
(166 reference statements)
1
12
0
4
Order By: Relevance
“…In diverse communities, the cost of moderation may disproportionately affect minority groups within the community. Aceros et al (2021) found that although activism can promote well-being and liberation, members of vulnerable groups may feel stress relating to the failure of systems to support their action and warn that community leaders may be especially prone to burnout. In the case of community academy, activism had positive outcomes at the individual family and community levels.…”
Section: Discussionmentioning
confidence: 99%
“…In diverse communities, the cost of moderation may disproportionately affect minority groups within the community. Aceros et al (2021) found that although activism can promote well-being and liberation, members of vulnerable groups may feel stress relating to the failure of systems to support their action and warn that community leaders may be especially prone to burnout. In the case of community academy, activism had positive outcomes at the individual family and community levels.…”
Section: Discussionmentioning
confidence: 99%
“…Los resultados del presente estudio dan a entender que esta situación lleva a la práctica el ideal feminista de politizar lo personal o, como afirma Magliano (2018), de defender que lo doméstico es político. Sin embargo, también sugieren que el activismo expone a las migrantes a vivenciar trauma vicario (Aceros et al, 2021), como les ocurre a profesionales que asisten a poblaciones en situación de vulnerabilidad. Adicionalmente, la lucha-cuidado implica que las migrantes reproduzcan en su actividad política el rol de cuidadoras que ejercen en sus familias y trabajos.…”
Section: Formas De Luchaunclassified
“…Debido a que el entorno relacional de las migrantes suele estar poblado por otras personas de origen extranjero (Fernández-Ocón & López-Olvera, 2009), esta labor de captación podría explicar la presencia exclusiva de mujeres latinoamericanas en la asociación, así como la ausencia de trabajadoras autóctonas. Además, aunque las mujeres son atraídas a la aths principalmente por los procesos de formación o servicios de asesoría jurídica, luego encuentran allí un espacio para socializar con otras migrantes (Aceros et al, 2021).…”
Section: Niveles De Implicaciónunclassified
See 2 more Smart Citations